TETABUHAN DALAM UPACARA NGABEN SEBUAH TINJAUAN MUSIKOLOGIS - I Nyoman Cau Arsana (SELONDING, 2012)
The study aims to explore the musical aspects of percussions in the process of Ngaben ritual with musicological approach. There are three types of percussion to be analyzed; Balaganjur Peponggangan, Gender Wayang, and Angklung. The analysis indicates that the processing of musical elements that include melody, rhythm, harmony, tempo, and dynamics established in the three types of percussions are quite harmonious with the ritual procession. This indicates a close relationship between the percussion and the ritual that reflects the concept of the Balinese Hindus on their culture and religion.   Keywords: Tetabuhan, Ngaben, Musical Aspect